Kajian Potensi Rotan di Hutan Desa Tumbang Habangoi Kabupaten Katingan : Study of Rattan Potential in the Community Forest of Tumbang Habangoi, Katingan Regency - Aguswan, Yusuf; Naibaho, Berto Dionisius; Toni, Hendra; Yusrivan, Redy; Mulawarman, Hasyim Asyari (HUTAN TROPIKA, 2024)
Katingan Regency is recorded as one of the regions with a significant production of Non-Timber Forest Products (NTFP), specifically rattan. In managing Community Forests, baseline data containing the potential resources within is required. This rattan potential data is used to formulate the Community Forest Management Plan. This study aims to estimate the potential of rattan in the Community Forest area of Tumbang Habangoi, Katingan Regency. Forest stand stratification was processed using the Forest Canopy Density (FCD) Model. The FCD is a vegetation index transformation developed by Rikimaru from the International Tropical Timber Organization – Japan Overseas Forestry Consultant Association (ITTO – JOFCA) and P.S. Roy from the Indian Institute of Remote Sensing in 1999, using Landsat TM imagery data as the primary input. The FCD results can distinguish canopy coverage with an accuracy of nearly 90%, enabling differentiation in canopy density. The FCD will be evenly distributed across 30 sample plots in the field. The number of sample plots, set at 30, is based on literature suggesting that a sufficient number of clustered image samples is around 25 evenly distributed sample plots. The rattan in the Community Forest of Tumbang Habangoi has an estimated total potential of approximately ±7,786.4 tons, averaging ±4.2 tons/ha. The growth of rattan heavily depends on the structure of the forest stands and the climbing trees supporting the rattan. The Forest Canopy Density Model is effective in mapping the horizontal structure of stands in Lowland Tropical Forests